On State Secession from International Law Perspectives - Lu, Jing (Springer International Publishing, 2018)
This book provides essential legal information on state secession in an innovative manner: unlike conventional approaches, which invariably focus on whether there is a right to secession, here the discussion centers on how secessionist conflicts can be effectively resolved. To that end, the book not only reveals the inadequacy of the current international legal framework, but also carefully considers how relevant actors can work to improve the legal system. In short, it argues that secessionists and non-secessionists should conclude an agreement to reconcile their conflicting rights to self-determination, while external actors should do their utmost to ensure the success of these efforts. Positive external involvement requires external actors to refrain from the use of force and to participate more rationally in secessionist conflicts. Given its subject matter, the book will appeal to a broad readership, including students and researchers in international law, international relations and ethnic studies, as well as enthusiasts in these fields.